Type 2 Diabetes Mellitus Status with Ankle-Brachial Index among Patients with Diabetic Foot Ulcer at Universitas Airlangga Hospital, Surabaya - Anisah, Hana; Limanto, Danang Himawan; Suryantoro, Satriyo Dwi; Utomo, Budi; Permana, Putu Bagus Dharma (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2024)
Highlights: ABI was not influenced by diabetic status due to potential confounders. A more severe form of diabetic ulcer was associated with a lower ABI value.   Abstract Introduction: Diabetic foot ulcer (DFU) is one of the most significant complications of uncontrolled type 2 diabetes mellitus (T2DM) that may affect a patient's prognosis and quality of life. This study aimed to identify the association between diabetic status, DFU severity, and other clinical factors with ankle-brachial index (ABI) score and category. Methods: This was a cross-sectional study under a consecutive sampling frame conducted from 1 November 2022 to 31 January 2023 at Universitas Airlangga Hospital, Surabaya. Primary data for ABl were measured from T2DM patients with DFU in the Thoracic and Cardiovascular Polyclinic. Meanwhile, secondary clinical data were collected from the Department of Internal Medicine based on the inclusion and exclusion criteria specified in the patient's medical records. The International Business Machines Corporation (IBM) Statistical Package for Social Sciences (SPSS) version 26 was utilized for the statistical analysis. Results: Out of 30 included patients, 63.33% had uncontrolled diabetic status, and the average ABI score was 0.999 ± 0.19. DFU severity was significantly associated with the ABI score and ABI category. Patients indicated with angioplasty exhibited a markedly lower ABI score than those without (mean 0.32 vs 1.01; p < 0.001). Indication of angioplasty was the only clinical factor significantly associated with a lower ABI score (p < 0.001). Conclusion: The status of T2DM was unrelated to ABI. Future research is recommended to advance the understanding of peripheral artery disease in diabetic foot ulcer patients.